2009
DOI: 10.1111/j.1471-4159.2009.06099.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor receptor‐associated protein 1 regulates cell adhesion and synaptic morphology via modulation of N‐cadherin expression

Abstract: 1 These authors contributed equally to this study.Abbreviations used: DiI, 1,1¢-dioctadecyl-3,3,3¢,3¢-tetramethylindocarbocyanine perchlorate; HSP90, heat shock protein 90; PBS, phosphate buffered saline; siRNA, small interfering RNA; siTRAP1, siRNAs against TRAP1; SNP, single nucleotide polymorphism; STAT, Signal Transducers and Activator of Transcription; TBS, Tris-bufferd saline; TNF, tumor necrosis factor; TNFR, tumor necrosis factor receptor; TRAP1, tumor necrosis factor receptor-associated protein 1. Abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 57 publications
(59 reference statements)
0
34
1
Order By: Relevance
“…In this study, we show significant site-specific decreases in DNA methylation in the promoter region of ARG2 and AMD1 that are correlated with the increases in levels of expression of these genes in suicide completers. Although we have not investigated the exact mechanism by which DNA methylation may act on the expression of ARG2 and AMD1, a recent study by Kubota and colleagues showed that decreases in E2F transcription factor 1 (E2F-1) are associated with decreased expression of genes related to the pathogenesis of major depression (Kubota et al, 2009). Interestingly, our results show decreases in DNA methylation in the promoter region of ARG2 and AMD1 in an area where E2F-1 is predicted to bind.…”
Section: Discussioncontrasting
confidence: 57%
“…In this study, we show significant site-specific decreases in DNA methylation in the promoter region of ARG2 and AMD1 that are correlated with the increases in levels of expression of these genes in suicide completers. Although we have not investigated the exact mechanism by which DNA methylation may act on the expression of ARG2 and AMD1, a recent study by Kubota and colleagues showed that decreases in E2F transcription factor 1 (E2F-1) are associated with decreased expression of genes related to the pathogenesis of major depression (Kubota et al, 2009). Interestingly, our results show decreases in DNA methylation in the promoter region of ARG2 and AMD1 in an area where E2F-1 is predicted to bind.…”
Section: Discussioncontrasting
confidence: 57%
“…This seems to be mediated by higher expression of genes promoting cell-cell and cell-matrix adhesion like cadherins, which are known to play critical roles in the processes of invasion and metastasis [27]. Moreover, Kubota et al [28] have reported that siRNA-mediated knockdown of TRAP1 in a neuronal cell line resulted in down-regulation of N-cadherin and affected the adhesive properties of the cells.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, ␦-catenin is involved in spine morphogenesis via the regulation of small RhoGTPases (5, 19). Moreover, tumor necrosis factor (TNF)-␣/TNF receptor signaling, which is implicated in the pathogenesis of major depression, was shown to be important to maintain N-cadherin expression that is required for normal spine morphogenesis (175). Thus spine morphogenesis by cadherins seems to be regulated in various ways.…”
Section: Synapse Formationmentioning
confidence: 99%